Rice Plant Protection System Against Planthopper Pests By Utilizing Ultrasonic Waves Using Direct Digital Synthesizer - Rahmat Nur Setiyanto (Politeknik Negeri Semarang, 2016)
-the largest pest Attacks against rice plant is pest. The most extermination of peasants is to use pesticides, but improper use of pesticides can thus cause a lot of losses. To overcome these physical methods used by utilizing ultrasonic wave with wave generator uses Direct Digital synthesizers. On the research of the testing was performed against the pest the pest by using frequency range audiosonik i.e. 1100 Hz – 5000 Hz and ultrasonic range i.e. 20 KHz to 60 KHz.